2003
DOI: 10.1182/blood-2003-03-0703
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of C5a-induced inflammation with preserved C5b-9-mediated bactericidal activity in a human whole blood model of meningococcal sepsis

Abstract: The complement system plays an important role in the initial defense against Neisseria meningitidis. In contrast, uncontrolled activation in meningococcal sepsis contributes to the development of tissue damage and shock. In a novel human whole blood model of meningococcal sepsis, we studied the effect of complement inhibition on inflammation and bacterial killing. Monoclonal antibodies (mAbs) blocking lectin and alternative pathways inhibited complement activation by N meningitidis and oxidative burst induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 59 publications
11
93
1
1
Order By: Relevance
“…In fact, TCC formation was slightly enhanced in the presence of anti-C5a. This observation may seem surprising at first glance but is consistent with previous data obtained when using this antibody to inhibit bacteria-induced C5a effects (50). The increased TCC formation cannot be explained by immune-complex formation because we excluded this possibility by experiments performed when this antibody was characterized (12).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, TCC formation was slightly enhanced in the presence of anti-C5a. This observation may seem surprising at first glance but is consistent with previous data obtained when using this antibody to inhibit bacteria-induced C5a effects (50). The increased TCC formation cannot be explained by immune-complex formation because we excluded this possibility by experiments performed when this antibody was characterized (12).…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, MAC is known to play a major role in meningococcal killing. Anti-C5 antibodies that block C5a and MAC formation were found to interfere with bacterial lysis using a human whole blood model of meningococcal sepsis (52). However, this study also showed that C5a-specific antibodies (monoclonal antibody 137-126) can bind the C5a moiety and inhibit the harmful effects of C5a while preserving MAC-mediated bacterial killing (52).…”
Section: Figurementioning
confidence: 94%
“…Heat-inactivated bacteria were used for safety reasons. Heat inactivation causes only minor alterations to the bacterial membrane, and the biological activity is preserved (54).…”
Section: Methodsmentioning
confidence: 99%